Overcoming Pseudomonas aeruginosa in Chronic Suppurative Lung Disease: Prevalence, Treatment Challenges, and the Promise of Bacteriophage Therapy - Jagdev Singh; Melinda Solomon; Jonathan Iredell; Hiran Selvadurai (Antibiotics)
Pseudomonas aeruginosa, a multidrug-resistant pathogen, significantly impacts patients with chronic respiratory conditions like cystic fibrosis (CF) and non-CF chronic suppurative lung disease (CSLD), contributing to progressive lung damage and poor clinical outcomes. This bacterium thrives in the airway environments of individuals with impaired mucociliary clearance, leading to persistent infections and increased morbidity and mortality. Despite advancements in management of these conditions, treatment failure remains common, emphasising the need for alternative or adjunctive treatment strategies. Bacteriophage therapy, an emerging approach utilising viruses that specifically target bacteria, offers a potential solution to combat P. aeruginosa infections resistant to conventional antibiotics. This review examines the prevalence and disease burden of P. aeruginosa in CF and CSLD, explores the mechanisms behind antibiotic resistance, the promising role of bacteriophage therapy and clinical trials in this sphere.